Geotourism potential of South Klias Peninsula, Sabah - Junaidi Asis; S.H. Tahir; Baba Musta; Hazerina Pungut; B. Jasin (Faculty of Science and Natural Resources, 2020)
The study area located at the Klias Peninsula consists of the Temburong Formation, Crocker Formation, Setap Shale Formation and Belait Formation. This research focus on the sedimentology of study area and to proposed geosites for geotourism potential. The sedimentology study is based on field data and the facies analysis. Geosite was evaluated to see the uniqueness based on the geological heritage value and the aesthetic value. Based on the facies analysis, the Temburong Formation was dominated by the outer lobe and basin plain facies association are interpret as outer fan and the Crocker Formation was dominantly by the channelized lobe and non-channelized lobe which is interpret as middle fan of deep marine turbidite system. The setap shale Formation consists of heterolitic sediment with some limestone lense interprate as shallow marine environment. Foraminifera analysis from the Temburong, Crocker and Setap Shale in study area consist of planktonic foraminifera range from Late Oligocene to mid Early Miocene for the Temburong Formation, late Early Miocene for the Crocker Fromation and Tea for the Setap Shale Formation which is slightly difference from the previous work. Three geosite have been identified for the geotourism potential in study area namely, Geosite 1 – Batu Luang unconformity of Setap Shale and Belait Formation, Geosite 2 – Batu Linting Hill of Crocker Formation and Geosite 3 – Tanjung Lambidan of Temburong Formation.